A CORRELATIVE STUDY OF CALCIFEROL WITH HOMOCYSTEINE, FOLIC ACID, AND COBALAMIN IN THE PATIENTS OF ALZHEIMER’S DISEASE: A CASE-CONTROL STUDY - Pooja Vashistha; Apoorva Bansal; Surendra Pratap Mishra; Ashok Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Alzheimer's disease is a degenerative irreversible brain condition that gradually damages memory, reasoning, and abilities, and ultimately the ability to effectively carry out the most basic tasks. Low level of vitamin D might be the risk factor of Alzheimer's disease. Insufficient levels of folic acid may cause hyperhomocysteinemia, which may lead to oxidative stress in brain tissue and harm neurons.Aim: The motive of the study was to find out the association and correlation of Vitamin level with folic acid, vitamin B12 and homocysteine in the subjects with Alzheimer’s disease.Method: This study was included 112 participants, out of these 56 cases and 56 control group. Patients having dementia were included in this study after taken ethical clearance certificate from IEC committee of BHU. Vitamin D, Homocysteine, folic acid and vitamin B12 were estimated for both group (Cases and control).Result: This study observed negative correlation of vitamin D with Homocysteine and folic acid and positive correlation with vitamin B12, which was found statistically not significant (p-vale >0.05).Conclusion: Vitamin D and folic acid deficiency is leading cause of Alzheimer’s disease, which can reduced homocysteine level and harm brain tissues.